ENCIRCLING GILLNET SELECTIVITY FOR OXEYE SCAD (Selar boops CUVIER, 1833) IN THE COAST OF WAAI, AMBON ISLAND - Grace Hutubessy (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The mesh selectivity of monofilament encircling gillnet for Oxeye scad (Cuvier,1833). Selar boops, was investigated using multi-panel of six different nets with mesh size of 1.50”, 1.75” and 2.00” (hang-in ratios 35% and 65% for each mesh size). Experimental fishing operation was carried out in the coastal area of Waai (Ambon Island) between September to November 2009. Probability of captured of oxeyescad was estimated using Holt’s method. Estimated optimum selectivity lengths for nets with 35% hang-in ratio were 14.33 cm for 1.50” mesh size, 16.74 cm for 1.75” mesh size and 19.11cm for 2.00” mesh size. Net with 65% hang-in ratio showed slightly larger optimum selectivity lengths (14.46 cm for 1.50” mesh size and 16.87 cm for 1.75” mesh size) then the other one.